Hot shape transformation: the role of PSar dehydration in stomatocyte morphogenesis - Peters, Remi; Charleston, Levy A.; van Eck, Karinan; van Berlo, Teun; Wilson, Daniela A. (Beilstein Journal of Organic Chemistry, 2025)
Polysarcosine emerges as a promising alternative to polyethylene glycol (PEG) in biomedical applications, boasting advantages in biocompatibility and degradability. While the self-assembly behavior of block copolymers containing polysarcosine-containing polymers has been reported, their potential for shape transformation remains largely untapped, limiting their versatility across various applications. In this study, we present a comprehensive methodology for synthesizing, self-assembling, and transforming polysarcosine-poly(benzyl glutamate) block copolymers, resulting in the formation of bowl-shaped vesicles, disks, and stomatocytes. Under ambient conditions, the shape transformation is restricted to bowl-shaped vesicles due to the membrane's flexibility and permeability. However, dehydration of the polysarcosine broadens the possibilities for shape transformation. These novel structures exhibit asymmetry and possess the capability to encapsulate smaller structures, thereby broadening their potential applications in drug delivery and nanotechnology. Our findings shed light on the unique capabilities of polysarcosine-based polymers, paving the way for further exploration and harnessing of their distinctive properties in biomedical research.
Keywords: biodegradable; poly(benzyl glutamate); polysarcosine; shape transformation; stomatocyte; supramolecular chemistry